Sensory approach to added sugar reduction in strawberry juices using fuyu persimmon - SALGADO, Derlyene Lucas; AMORIM, Katiúcia Alves; ANDRADE, Luan Alberto; RODRIGUES, Jéssica Ferreira; CURI, Paula Nogueira; de SOUZA, Vanessa Rios; BASTOS, Sabrina Carvalho; PINHEIRO, Ana Carla Marques (Food Science and Technology, 2024)
The aim of this study was to produce strawberry juice with reduced added sugar content, use the alternative natural sweetness of persimmon, and evaluate its physicochemical and sensory characteristics. Five different strawberry juice formulations were prepared with a 25% reduction in the added sucrose content with 0, 12.5, 25, 37.5, and 50% added persimmon pulp. Color, soluble solids, pH, and titratable acidity were evaluated, and CATA and acceptance sensory tests were performed with 100 consumers. In general, adding persimmon pulp to strawberry juice significantly affects both its physicochemical and sensory properties. From a physicochemical point of view, as the persimmon content increased, the strawberry juice tended to turn from red to orange, and there was an increase in soluble solids content and pH, as well as a decrease in acidity. From a sensory point of view, changes in sensory profile and product acceptability were also observed. However, persimmon showed potential as a natural sweetener in strawberry juice to reduce added sugar. Formulations with lower levels of persimmon pulp (12.5 and 25%) showed promise as these formulations maintained the valued sensory characteristics of strawberry juice and used the natural sweetness of persimmon to reduce added sugars, making them healthier beverage alternatives.